2011
DOI: 10.1111/j.1748-1716.2011.02337.x
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic lateral sclerosis immunoglobulins G enhance the mobility of Lysotracker-labelled vesicles in cultured rat astrocytes

Abstract: Amyotrophic lateral sclerosis-IgG-enhanced vesicle mobility in astrocytes engages changes in calcium homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 80 publications
(154 reference statements)
1
27
0
Order By: Relevance
“…Overall, the IgG from the control group evoked calcium transients in 7.7 ± 3.9% of cells, whereas ALS IgG evoked a change in 47.5 ± 12.9% of cells, significantly higher (p = 0.0158, Fig. 1F), indicating that ALS IgG strongly affects astrocytic calcium homeostasis, as considered by Stenovec et al [26].…”
Section: Als Igg Evokes Cytosolic Calcium Transients In Astrocytesmentioning
confidence: 56%
See 3 more Smart Citations
“…Overall, the IgG from the control group evoked calcium transients in 7.7 ± 3.9% of cells, whereas ALS IgG evoked a change in 47.5 ± 12.9% of cells, significantly higher (p = 0.0158, Fig. 1F), indicating that ALS IgG strongly affects astrocytic calcium homeostasis, as considered by Stenovec et al [26].…”
Section: Als Igg Evokes Cytosolic Calcium Transients In Astrocytesmentioning
confidence: 56%
“…Our results show that ALS IgG stimulates the release of Ca 2+ from intracellular calcium stores and through plasma membrane SOCEs, which remain to be identified. Furthermore, in a subset of experiments, for which we used the same ALS IgG as in our mobility study of lysotracker-stained acidic vesicles [26], we found a moderate (correlation coefficient R = 0.35) and significant (p < 0.001) positive correlation between the peak increase in [Ca 2+ ] i and the change in vesicle maximal displacement [26] evoked by ALS IgG (data not shown). In agreement with previous functional and neuro-immunological studies in neurons [11,12,14,37] and in astrocytes [26], IgG from patients with sALS, but not from control individuals without ALS, evoked rather complex and transient increases in [Ca 2+ ] i in ∼48% of treated astrocytes (Fig.…”
Section: Numerous Cultured Astrocytes Respond To Als Igg Treatment Bymentioning
confidence: 68%
See 2 more Smart Citations
“…This deficient astroglial phenotype may be associated with changes in the traffic of intracellular vesicles. In astrocytes exposed to antibodies isolated from ALS patients, a massive alteration in vesicle dynamics and Ca 2+ homeostasis has been reported [79,80]. In the animal model of ALS expressing human mutant superoxide dismutase 1 (Tg(SOD1*G93A)1Gur mice), the emergence of atrophic astrocytes is the earliest pathological signature [81][82][83]; these atrophic astrocytes down-regulate glutamate uptake and become vulnerable to glutamate by themselves.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%